Pengaruh Penerapan Etika Profesi Staf Perpustakaan Terhadap Kepuasan Mahasiswa Dalam Penggunaan Layanan Perpustakaan (Studi Empiris pada Mahasiswa Universitas Negeri Medan) - Trianingsih, Hoza; Pramesti, Nindy Jaya (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the impact of the implementation of professional ethics by library staff on student satisfaction in utilizing library services at Universitas Negeri Medan. Using a quantitative method with a survey approach, data were collected from 50 students who regularly use library services. The linear regression analysis results indicate that the implementation of professional ethics by library staff has a significant and positive effect on student satisfaction. The F-test yielded a significance value of 0.000, indicating that the regression model is statistically significant. Additionally, the T-test shows that the variable of professional ethics implementation by library staff significantly influences student satisfaction. These findings highlight the importance of implementing professional ethics to enhance the quality of library services and user satisfaction